Audit of Seclusion: Evaluating Performance Against National and Local Standards - Sadia Tabassum Javaid; Raman Mittal; Qammar Jabbar; Corrina Bentley; Samantha Dawson (BJPsych Open, 2025)
Aims: Seclusion, under the Mental Health Act (MHA 1983) Code of Practice, is the supervised confinement of a patient to manage severe risks. The Mental Health Law Governance Group commissioned a clinical audit to assess compliance with the Trust’s Seclusion Policy and MHA Code of Practice, prioritised in the 2024–2025 Audit Programme.